ANALISIS BIAYA PRODUKSI DALAM MENENTUKAN HARGA JUAL MENGGUNAKAN METODE FULL COSTING PADA UMKM MAKANAKU BANDAR LAMPUNG - Rafagina Feby Rahmanti; Iskandar Ali Alam (Jurnal Widya, 2024)
This research aims to compare the methods used both variable costing and full costing as seen from the cost of production to determine the selling price at Makanaku Bandar Lampung. This research is a type of quantitative descriptive research. To find out the basic price and selling price of Makanaku Bandar Lampung, interviews and documentation were carried out, which were then analyzed quantitatively. Based on the research results and data analysis, it can be concluded that there is a difference between the full costing and variable costing methods, this is because the costs charged to products are only from variable costs. So that it will affect the determination of the cost of production and cost of goods sold, so that profits will also have an effect. The advice that can be given is to determine the selling price, the company should still take into account the cost of production and the expected profit percentage, so that the selling price information can be presented fairly. Because the market price is not always high. With information on calculating a reasonable selling price, it can be used as a basis for making decisions for the company, so that it can be considered in making decisions.